Gold Nanoparticle Synthesis Using Quercetin: Innovation in Biopreneur - Pertiwi, Ratih Dyah; Fitria, Pika Ayu; Utami, Tyas Putri; Pamungkas, Rian Adi; Pradana, Reinaldo; Chamroonsawasdi, Kanittha (Pandawan, 2025)
Biosynthesis offers an environmentally friendly approach for manufacturing nanoparticles, with flavonoids such as quercetin showing potential as reducing agents. This study aimed to synthesize gold nanoparticles (AuNPs) from HAuCl4 using quercetin as a reducing agent. The synthesis process was monitored using UV-Vis spectrophotometry, and the particle size and stability of the nanoparticles were characterized using a Particle Size Analyzer (PSA). The synthesized AuNPs exhibited a color change from light yellow to deep purple, with a peak absorbance between 500 600 nm. The average particle size was found to be 116.7 nm, with a zeta potential of -12.2 mV, and a polydispersity index of 0.293. The inhibitory activity of the AuNPs was assessed by their effect on the tyrosinase enzyme, yielding an IC50 value of 970 μg/mL. These results suggest that gold nanoparticles synthesized using quercetin are stable and exhibit potential inhibitory activity against tyrosinase. The study concludes that this green synthesis method has the potential for further development in drug delivery systems, providing an innovative approach in biopreneurship.